Value chain analysis of the bean sector in north Kivu: market dynamics, governance structures, and economic performance in the city of Goma - Eric Nice NSHEMBE CHISHUNGU; Jeannot KAVUYA KATYA (International Journal of Scientific Research and Innovative Studies, 2026)
This study analyses the bean value chain in North Kivu, Democratic Republic of Congo, with a particular focus on market dynamics, governance structures, and economic performance in the city of Goma. A mixed-methods approach was applied using survey data collected from 250 respondents, including producers, wholesalers, retailers, transporters, consumers, and institutional actors across the principal bean markets of Goma. Descriptive statistics, gross margin analysis, Benefit–Cost Ratios (BCR), ANOVA, Pearson correlation, and Chi-square tests were employed to evaluate profitability and governance relationships along the chain. Results indicate that bean yields remain low, varying from 400 kg/ha to 1200 kg/ha due to limited access to improved seeds, fertilizers, and phytosanitary inputs. Producer revenues range between USD 175 and USD 825 per hectare, while value added varies from USD 25 to USD 715/ha. Profitability levels are highly differentiated, with BCRs ranging from 1.17 to 7.50 depending on yield, quality, and production costs. Transport costs significantly affect market integration and wholesaler margins, varying between USD 8 and USD 16 per 160-kg bag. Pearson correlation analysis confirms a strong negative relationship between transport costs and wholesaler profitability (r = −0.84; p = 0.037). Governance structures are dominated by wholesalers who coordinate price formation and market flows. Semi-wholesalers earn approximately USD 13–15 per bag, while retailers achieve the highest margins through final consumer sales ranging from USD 0.94 to USD 1.50/kg. The study concludes that improving seed access, transport infrastructure, storage systems, and cooperative marketing mechanisms is essential for enhancing efficiency, equity, and resilience within the bean value chain in North Kivu. Keywords: value chain, beans, market dynamics, governance, North Kivu. Received Date: February 22, 2026 Accepted Date: March 14, 2026 Published Date: April 02, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/667